USING J-QUERY MOBILE TECHNOLOGY TO SUPPORT A PEDAGOGICAL PROFICIENCY COURSE - Kert, Serhat Bahadir (SAGE PUBLICATIONS INC, 2013)
Technology-enriched educational environments supported by different technological tools and applications are today's important research areas in the educational literature. During the educational process, different types of technologies are used in order to enhance the learning capabilities of students. Given the popularity of mobile phones, it can be said that mobile applications developed for educational purposes have remarkable potential as content and software diversity in terms of educational aspects. Within this context, a different kind of mobile learning software was developed and used during a pedagogical proficiency course in this study. The software named YTUMOB was developed by using 3-Query technology and was used as a support tool during a pedagogical proficiency course. Retrieving statistics of the mobile environment were recorded and analyzed. In order to examine the effectiveness of the system, assignment- and test-based evaluation results were used together and statistical comparisons were made between experimental and control groups of the study. All developing and conducting processes of the software were explained in detail. The results of the study revealed that differences between the academic success points of two groups were increased in time in favor of the group using mobile J-Query support.
Keywords: IMPLEMENTATION; Education & Educational Research